Answer: PN= 20 in.
Step-by-step explanation:
Given: In triangles PMN and QSR :
Length of P N ≅ Length of RQ (1) [ '≅' → Sign of congruence]
Length of QS ≅ Length of PM
Length of MN ≅ Length of RS
By SSS congruence rule
ΔPMN ≅ ΔQSR
Since Length of QR =20 in. [Given]
From (1)
Length of PN= 20 in. [Congruent means exactly equal]
Answer:
Its C brudda
Step-by-step explanation:
Ronaldo>Messi
and still have $35. How much money did Alexis receive for her birthday?
Answer:
$65
Step-by-step explanation:
65-30=35
Answer:
i cant like give you the answer off the top of my head but when i did this the video helped me a lot
Step-by-step explanation:
its How to Graph the line y = x by Cowan Academy
The equation you provided is a standard form equation for a circle. By comparing it to the general circle equation and taking square root of the constant on the right side, we find that the radius of the circle is 5.
The equation of a circle is typically given in the form (x - h)² + (y - k)² = r², where (h, k) is the center of the circle and r is the radius.
Therefore, the radius of the circle is 5.
#SPJ2
(2, 8) and (3, 14)
The equation of the line that passes through (2, 8) and (3, 14) will be y = 6x - 4.
A connection between a number of variables results in a linear model when a graph is displayed. The variable will have a degree of one.
Let the equation of the line pass through (x₁, y₁) and (x₂, y₂).
Then the equation of the line is given as,
The points are given below.
(2, 8) and (3, 14)
The equation of the line that passes through (2, 8) and (3, 14) will be given as,
(y - 8) = [(14 - 8) / (3 - 2)](x - 2)
y - 8 = 6x - 12
y = 6x - 4
The condition of the line that goes through (2, 8) and (3, 14) will be y = 6x - 4.
More about the line passing through two points link is given below.
#SPJ2
Answer:
6
Step-by-step explanation:
The slope is calculated by finding the change in y-coordinates and dividing that by the change in x-coordinates.
The change in y:
8-14=-6
The change in x:
2-3=-1
The slope:
Answer:
x = 14
Step-by-step explanation:
If H is the midpoint of GI, then
GI = 2GH
11x -10 = 2(5x +2)
11x -10 = 10x +4 . . . eliminate parentheses
x = 14 . . . . . . . . . . . . add 10-10x